2018
DOI: 10.1177/1468017318814996
|View full text |Cite
|
Sign up to set email alerts
|

Explaining the policy practice of community social workers

Abstract: Summary Policy change is a core goal of community social workers. This study aims to identify the motivational and facilitating factors associated with community social workers’ engagement in policy practice, defined as policy involvement undertaken in the workplace context. The sample comprised of 106 community social workers employed by local government in Israel and the data were collected between June 2015 and February 2017. Findings The findings showed that community social workers are more likely to enga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 45 publications
(49 reference statements)
2
22
0
Order By: Relevance
“…These classroom projects can create an interest and commitment among students during their training to actively engage in community practice after their graduation. In fact, studies show that macro-practice training during graduate studies is positively associated with PPE in the community (Reisch, 2016; Weiss-Gal & Gal, 2018).…”
Section: Discussion and Pedagogical Implicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…These classroom projects can create an interest and commitment among students during their training to actively engage in community practice after their graduation. In fact, studies show that macro-practice training during graduate studies is positively associated with PPE in the community (Reisch, 2016; Weiss-Gal & Gal, 2018).…”
Section: Discussion and Pedagogical Implicationsmentioning
confidence: 99%
“…To this end, social work faculty and researchers have identified community projects and policy advocacy action projects to develop macro-practice skills and learning outcomes through innovative assignments. Some of these action projects include the use of experiential advocacy assignment (Manalo, 2004), case-based collaborative learning model (Kilbane, Freire, Hong, & Pryce, 2014), practising policy, pursuing change and promoting social justice (3P) approach (Heidemann, Fertig, Jansson, & Kim, 2011), advocacy week model (Kilbane, Pryce, & Hong, 2013), internet-based assignment (Tower & Hartnett, 2011) and policy practice engagement (PPE) model (Pawar, 2019; Weiss-Gal & Gal, 2018). The findings of these studies document how creative assignments have been used to achieve macro-practice skills.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional studies have examined the ethical dilemmas community practitioners may encounter (Hardina, 2004), the factors contributing to their involvement in the policy arena (Weiss- Gal & Gal, 2018), and the characteristics and motivations of community members (Zanbar & Ellison, 2019;Zanbar & Itzhaky, 2018). Scholars have also debated the question of whether community social work today has a radical potential (Butcher, Banks, Henderson, & Robertson, 2007;Ledwith, 2011).…”
Section: The Missing Voice In Community Practice Literaturementioning
confidence: 99%
“…Motivational factors encompass the personal perceptions, experiences, and acquired knowledge and skills that professionals possess, and that lead to a willingness to engage in policy‐related activities as part of their professional endeavors. Existing research based on the PPE framework has shown that three types of individual motivation factors are linked to the policy engagement of care professionals (Weiss‐Gal & Gal, 2020). The first of these are personal resources, which include skills and professional status.…”
Section: Introductionmentioning
confidence: 99%